Glucagon-Like Peptide-2 Analogue ZP1849 Augments Colonic Anastomotic Wound Healing. (9th October 2020) - Kjaer, Marie; Russell, Wayne; Schjerling, Peter; Cottarelli, Elena; Christjansen, Kennet N.; Olsen, Ditte M. G.; Krarup, Peter-Martin; Jessen, Lene; Berner-Hansen, Mark; Jorgensen, Lars N.; Ågren, Magnus S.
Abstract : Background . The enteroendocrine hormone glucagon-like peptide- (GLP-) 2 is a potent trophic factor in the gastrointestinal tract. The GLP-2 receptor (GLP-2R) is expressed in the stroma of the large bowel wall, which is the major therapeutic target area to prevent anastomotic leakage. We investigated the efficacy of the long-acting GLP-2 analogue ZP1849 on colonic anastomotic wound healing. Methods . Eighty-seven male Wistar rats were stratified into four groups and received daily treatment with vehicle or ZP1849 starting one day before (day -1) end-to-end anastomosis was constructed in the left colon on day 0, and on days 0 (resected colon segment), 3, and 5, gene expressions of GLP-2R, Ki67, insulin-like growth factor- (IGF-) 1, type I (COL1A1) and type III (COL3A1) procollagens, cyclooxygenase- (COX-) 1, COX-2, and matrix metalloproteinase- (MMP-) 7 were quantified by RT-qPCR. Breaking strength, myeloperoxidase (MPO), transforming growth factor- (TGF-) β 1, and soluble collagen proteins were measured on days 3 and 5. Results . ZP1849 treatment increased Ki67 (P < 0.0001 ) and IGF-1 (P < 0.05 ) mRNA levels in noninjured colon day 0, and postoperatively in the anastomotic wounds compared to vehicle-treated rats. ZP1849-treated rats had increased (P = 0.042 ) anastomotic breaking strength at day 5 compared with vehicle. COL1A1 and COL3A1 mRNA levels (P < 0.0001 ) and soluble collagen proteins (P < 0.05 ) increased from day 3 to day 5 in ZP1849-treated rats, but not in vehicle-treated rats. COX-2 mRNA and MPO protein levels decreased from day 3 to day 5 (P < 0.001 ) in both groups. ZP1849 treatment reduced TGF- β 1 protein levels on day 5 (P < 0.001 ) but did not impact MMP-7 transcription. Conclusions . The GLP-2 analogue ZP1849 increased breaking strength, IGF-1 expression, and cell proliferation, which may be beneficial for colonic anastomotic wound healing.